CROSS-BORDER LISTINGS AND PRICE DISCOVERY. EVIDENCE FROM CHINESE COMPANIES TRIPLE-LISTED IN SHANGHAI, HONG KONG AND NEW YORK - YANG , Xiaoou; KUN , Peng (Journal of Advanced Studies in Finance; Vol 5 No 1 (2014): JASF Volume V, Issue 1(9), Summer, 2014, 2014)
This paper extends prior cross-listing literature by examining the Chinese stocks triple-listed in Hong Kong Stock Exchange (SEHK), Shanghai Stock Exchange (SSE) and New York Stock Exchange (NYSE). We find that the returns of the triple-listed stocks and the indexes are co-integrated in the long-run across the three markets, indicating both an absence of arbitrage opportunities and long-term equilibrium. By employing the Granger Causality test, we found that the foreign market (NYSE) plays the dominant role in price discovery (where information is impounded into prices), therefore rejecting the home bias hypothesis that the home market generates the most useful information about price movement. While the stock returns of NYSE were able to influence the returns of both the SSE and the SEHK, the SSE market could not affect the NYSE and only on rare occasions affects the SEHK. The same methodology to examine the co-integration and price discovery were employed for 4 distinctive sub-periods: 2000-2003, 2003-2007, 2007-2009, and 2009-2013. It was found that while China was a relatively independent market prior to the financial crisis, its integration with the global markets has increased ever since.